Análise multitemporal do uso e cobertura da terra no município de Primavera-PA, utilizando os dados do Projeto TERRACLASS de 2008 a 2022 - SILVA, Paula Elayane Farias da (2024)
The work presents an analysis of the dynamics of land use and coverage in the municipality of Primavera, Pará, considering temporal changes in the years 2008, 2012, 2018 and 2022, based on data from the TerraClass Project,subsequently, dynamics analyzes were carried out and comparisons were made between the mappings. The choice of this municipality as the unit of analysis is particularly relevant, given the impact of human activities, such as the installation of a Votorantim cement factory (installed in 2016); as well as advances in environmental preservation with the creation of the Filhos do Mangue Marine Extractive Reserve (2024), which have directly influenced land use and local environmental characteristics. The methodology included bibliographic research and use of QGIS software to categorize and vectorize maps, resulting in systemic maps with temporal themes. The results observed indicate a significant reduction in natural forest vegetation, replaced by pastures (39.7% in 2022), highlighting the impact of human activities, such as agriculture and urbanization, on the local landscape and economy. This study on land use and cover in Primavera/PA highlights how human intervention shapes the natural landscape, directly influencing the environment and the economy. Geospatial analysis, especially in poorly documented areas, is essential for making informed decisions, aiming to strike a balance between economic development and environmental preservation.